PEMBERDAYAAN GURU DAN SISWA SMK NEGERI 3 KECAMATAN PAHUNGA LODU, KABUPATEN SUMBA TIMUR MELALUI PELATIHAN DESAIN STIKER KEMASAN STIK RUMPUT LAUT [EMPOWERMENT OF TEACHERS AND STUDENTS OF SMK NEGERI 3 PAHUNGA LODU, EAST SUMBA REGENCY THROUGH TRAINING PACKAGING DESIGN OF SEAWEED STICKS PRODUCTS] - Firat Meiyasa; Nurbety Tarigan; Yatris Rambu Tega; Suryaningsih Ndahawali; Lusianus Heronimus Sinyo Kelen; Vindya Donna Adindarena; Yulita Milla Pakereng (Universitas Pelita Harapan, 2020)
Packaging has a very important role to increase shelf life and the economic value of food products. In addition, packaging is able to attract attention of consumers so that they are interested in buying these food products. The purpose of this community service activity is that teachers and students of SMK Negeri 3 Pahungga Lodu are able to independently design packaging stickers for seaweed stick products. The method included giving materials, training in packaging design by using microsoft power point, making stick products, and accompanying of teachers and students. The results of the community service activity are in the form of seaweed stick products, knowledges and skills to produce packaging stickers for seaweed stick products. This community service activity received a positive response from teachers and students of SMK Negeri 3 Pahunga Lodu in the form of knowledge about the manufacture of seaweed stick products and attractive packaging sticker designs for seaweed stick products.BAHASA INDONESIA ABSTRACT: Kemasan memiliki peranan yang sangat penting untuk meningkatkan umur simpan dan menambah nilai ekonomis pada produk pangan. Selain itu, kemasan juga mampu menarik perhatian konsumen sehingga konsumen tertarik untuk membeli produk pangan tersebut. Tujuan dari kegiatan pengabdian kepada masyarakat ini adalah guru dan siswa mampu membuat desain stiker kemasan secara mandiri untuk produk stik rumput laut yang dihasilkan oleh SMK Negeri 3 Pahungga Lodu. Metode pelaksanaan pengabdian ini meliputi: pemberian materi, pelatihan desain kemasan menggunakan Microsoft Power Point, tahap pembuatan produk stik, dan pendampingan pada guru dan siswa. Hasil dari kegiatan pengabdian ini adalah berupa produk stik rumput laut, pengetahuan dan keterampilan dalam menghasilkan desain stiker kemasan untuk produk stik rumput laut. Kegiatan pengabdian ini mendapatkan respon positif dari guru dan siswa SMK Negeri 3 Pahunga Lodu berupa pengetahuan tentang pembuatan produk stik rumput laut dan desain stiker kemasan yang menarik untuk produk stik rumput laut.